ON HYPERRINGS ASSOCIATED WITH BINARY RELATIONS ON SEMIHYPERGROUP - Jančić Rašović, Sanja (Italian Journal of Pure and Applied Mathematics, 2013)
In this paper we construct a class of hyperrings associated with binary relations on semihypergroup. We establish a connection between the constructed hyperring (H, + ρ1 , ◦ ρ2) and the hyperring of multiendomorphisms of hypergroup (H, + ρ1 ). Also, we analyze subclasses of the constructed class, which are associated with partial orderings on a set of multimappings.